Search for methylation-sensitive amplification polymorphisms in mutant figs - Rodrigues, M. G F; Martins, A. B G [UNESP]; Bertoni, B. W.; Figueira, A.; Giuliatti, S. (Genetics and Molecular Research, 2013)
Fig (Ficus carica) breeding programs that use conventional approaches to develop new cultivars are rare, owing to limited genetic variability and the difficulty in obtaining plants via gamete fusion. Cytosine methylation in plants leads to gene repression, thereby affecting transcription without changing the DNA sequence. Previous studies using random amplification of polymorphic DNA and amplified fragment length polymorphism markers revealed no polymorphisms among select fig mutants that originated from gamma-irradiated buds. Therefore, we conducted methylation-sensitive amplified polymorphism analysis to verify the existence of variability due to epigenetic DNA methylation among these mutant selections compared to the main cultivar 'Roxo-de-Valinhos'. Samples of genomic DNA were double-digested with either HpaII (methylation sensitive) or MspI (methylation insensitive) and with EcoRI. Fourteen primer combinations were tested, and on an average, non-methylated CCGG, symmetrically methylated CmCGG, and hemimethylated hmCCGG sites accounted for 87.9, 10.1, and 2.0%, respectively. MSAP analysis was effective in detecting differentially methylated sites in the genomic DNA of fig mutants, and methylation may be responsible for the phenotypic variation between treatments. Further analyses such as polymorphic DNA sequencing are necessary to validate these differences, standardize the regions of methylation, and analyze reads using bioinformatic tools. © FUNPEC-RP.
Keywords: DNA methylation; Epigenetic inheritance; Molecular marker; Mutation analysis; Plant breeding; cytosine; genomic DNA; guanine; type II site specific deoxyribonuclease; cultivar; DNA determination; epigenetics; fig; gene amplification; genetic polymorphism; genetic selection; genetic variability; mutant; nonhuman; nucleotide binding site; phenotypic variation; sensitivity analysis